2009
DOI: 10.1021/ac902459m
|View full text |Cite
|
Sign up to set email alerts
|

Linearized Equations for the Reduced Ion Mobilities of Polar Aliphatic Organic Compounds

Abstract: Over the years, ion mobility spectrometry has evolved into a powerful technique for rapid identification of analytes in very complex sample matrixes such as human breath. Every analyte detected has a characteristic ion mobility value (and a retention time when additional preseparation techniques are employed) which is used to identify the peaks in a spectrum either by comparison with reference analytes or by simultaneous mass spectrometric measurements. In this study, the mass-mobility correlations between com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In [20], linear dependences 1/K 0 versus N(C) were obtained for alcohols, aldehydes, and ketones. Since the value of 1/K 0 is proportional to the collision cross section, the authors suggested that the collision cross section could be presented in the form of two components.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In [20], linear dependences 1/K 0 versus N(C) were obtained for alcohols, aldehydes, and ketones. Since the value of 1/K 0 is proportional to the collision cross section, the authors suggested that the collision cross section could be presented in the form of two components.…”
Section: Resultsmentioning
confidence: 97%
“…However, the above works are of an applied character and do not deal with questions of the structure of the formed ions. Considering homological series [20][21][22], which allows us to find correlations between the molecular weight and ionic mobility of organic compounds in the gas phase, is useful. In this work, the structure of ions of the monomers and dimers formed by aldehydes in the gas phase is investigated by means of ion mobility spectrometry in combination with ab initio quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In this study they discovered a linear relation between the number of carbon atoms and the reduced ion mobility of the compounds within a certain homologous series, as a fast and intuitive method for K 0 estimation [74]. …”
Section: Statistical Learningmentioning
confidence: 99%
“…While this software package is designed to work with National Instrument hardware, the programmatic structure and hardware requirements outlined below may also serve as a framework for development in more open architectures. Recent work by Hariharan, et al shows promise towards identification of unknown IMS spectral peaks through linearization and database analysis [17]. This functionality should prove to be easily adaptable to the software system presented herein and provide stand-alone IMS instruments with capabilities previously reserved for tandem methods.…”
Section: Introductionmentioning
confidence: 97%